THE IMPORTANCE OF GLUCOSE DETERMINATION IN THE BLOOD OF THE CYPRINIDS - TANŢI PATRICHE (Scientific Papers Animal Science and Biotechnologies, 2023)
The range of paraclinical investigations applied in ichthyopathology aims at assessing those parameters biocemical that can define the pathological modifications and the normal physiological condition of the fish materia. Modification in value of these indicators points out some metabolic perturbations in fish body. To be aware of the health condition of the biological material in a fish farm allows us to stablish the preventive measures required to prevent spreading of a disease and the treatment to be applied in case that a mass disease occurs. That is why to know the value of the serical glycemia enables us to differentiate the normal physiological condition of the fish material under research from the eventual pathological modifications having occurred due to the defence reaction of the organism, the first representing a high value marker indicator of the stress condition (Kebus and colab., 1992; De Dominis and colab., 1993; Barry and colab., 1993; Bau and colab., 1994; Rehulka, 1996).